Curdlan acetate fibres with low degrees of substitution fabricated via a continuous process of chemical modification and wet spinning using an ionic liquid. Issue 6 (4th March 2022) - Suzuki, Shiori; Togo, Azusa; Kimura, Satoshi; Iwata, Tadahisa
Abstract : Curdlan was acetylated with a low degree of substitution (DS), and the reaction solution was subjected to wet spinning. The curdlan acetate fibres showed the changes in the crystalline structure and the wet-to-dry tenacity at the DS exceeding 0.8. Abstract : Polysaccharide esters with a low degree of substitution (DS) are expected to be biomass-derived biodegradable plastics with tunable properties that will replace conventional petroleum-derived plastics. However, they have difficulties in moulding and complex multistep synthesis is required to control their DS, thereby limiting their application as plastics. In this study, we demonstrate a continuous process of homogeneous acetylation of curdlan (β-1, 3-glucan) and direct wet spinning of the reactant solution by consistently using an ionic liquid, and achieve both facile and green synthesis and fabrication of curdlan acetate fibres with the DS ranging from 0.1–1.0. The partial acetylation of curdlan improved the thermal stability and fiber properties: thermal degradation temperature ( T d-5% ) from 293 to 342 °C, Young's modulus (dry) from 2.9 to 4.0 GPa, and wet tenacity from 0.34 to 2.8 cN tex −1 . Originally, a regenerated curdlan fibre was ductile with a high water absorbency of 85 wt% causing a considerable decrease in wet tenacity. In contrast, curdlan acetate fibres stiffened and the water absorbency was suppressed to 15 wt% at DS = 0.8 owing to the substitution of the C4-OH group (which contributed to the incorporation of water into the curdlan molecules). Consequently, the wet-to-dry tenacity ratio of the curdlan acetate fibres significantly improved from 0.03 to 0.5. Such enhanced properties were attributed to the change in the crystalline structure by acetylation at the DS exceeding 0.4 with preventing the formation of hydrogen bonding via the C2-OH group (which stabilised the original triple helical structure).